2009
DOI: 10.1111/j.1365-2761.2009.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of betanodavirus infection in tilapia, Oreochromis niloticus (L.), in fresh water

Abstract: A betanodavirus associated with a massive mortality was isolated from larvae of tilapia, Oreochromis niloticus, maintained in fresh water at 30 degrees C. Histopathology revealed vacuolation of the nervous system, suggesting an infection by a betanodavirus. The virus was identified by indirect fluorescent antibody test in the SSN1 cell line and further characterized by sequencing of a PCR product. Sequencing of the T4 region of the coat protein gene indicated a phylogenetic clustering of this isolate within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 17 publications
2
64
0
4
Order By: Relevance
“…In 2007, a betanodavirus was detected by RT-PCR in Nile tilapia larvae following a mass mortality event at a western European fish farm (Bigarré et al 2009), andEyngor et al (2014) isolated a novel RNA virus (tilapia lake virus) from wild tilapia and confirmed its pathogenicity via experimental infection in Nile tilapia.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, a betanodavirus was detected by RT-PCR in Nile tilapia larvae following a mass mortality event at a western European fish farm (Bigarré et al 2009), andEyngor et al (2014) isolated a novel RNA virus (tilapia lake virus) from wild tilapia and confirmed its pathogenicity via experimental infection in Nile tilapia.…”
Section: Introductionmentioning
confidence: 99%
“…Common ectoparasites and the few bacterial pathogens of tilapines are well controlled by pharmacotherapy. Few viral diseases have been reported for tilapia, and these are of limited impact (7)(8)(9).…”
mentioning
confidence: 99%
“…Betanoda virus ini menyerang larva ikan nila ukuran 0-7 setelah menetas (post-hatching larvae) dengan gejala adanya kerusakan jaringan pada bagian otak berupa vakuolasi (Bigarre et al, 2009 Jurnal Riset Akuakultur, 13 (1), 2018, 85-92 …”
Section: Bp Bpunclassified